PENINGKATAN EKONOMI KREATIF MELALUI INOVASI KEMASAN PADA PRODUK SERBUK JAHE UMKM LOKAL DI DESA MEKAR BERSATU, KECAMATAN BATUKLIANG, KABUPATEN LOMBOK TENGAH, NTB - Sutrawan, I Gede; Ariani, Ines; Puspatrinayanti, Ni Ketut; Salsabila, Baiq Safira Putri; Gazi, Nabila; Fakar, Hidayat Muslim; Kurniawan, Rivaldy; Kurniawati, Kurniawati; Suraya, Ayu; Hariadi, Hafiz Usamah (Universitas Mataram, 2024)
Mekar Bersatu Village, a small village in Batukliang District, Central Lombok Regency, faces several challenges, one of which is in terms of improving the economy of the community. In addition, this village also has various potentials that can be developed. UMKM are one potential solution to economic problems in the village. One of the potential UMKM is UD. Mak Hani which produces ginger powder. However, the quality of the packaging and the design of the packaging label that is less attractive are the main obstacles. For this reason, KKN PMD students from Mataram University in Mekar Bersatu Village provide solutions in the form of packaging updates and packaging label innovations. The purpose of this activity is to update the packaging to be more practical and innovate the packaging design by improving the packaging design to increase the economic value and creative economy of the village community, especially UMKM. This activity takes eight stages, including involving several methods such as surveys, interviews, determining the MSMEs involved, problem analysis, problem solving with SWOT analysis, to implementing solutions and product promotion. The results of this activity are in the form of ginger powder products with new packaging that is more practical and attractive. In addition, the results of this activity are in the form of more attractive and informative packaging labels. The target of this program also accepted the solutions provided. This activity is expected to continue and can provide a sustainable positive impact on the local economy.